THE RELATIONSHIP BETWEEN BSE KNOWLEDGE AND BREAST TUMOR SIZE DURING SURGICAL CENTER VISIT AT UNAIR HOSPITAL - Eva Silvia Yahya; Pungky Mulawardhana; Nila Kurniasari (Indonesian Midwifery and Health Sciences Journal, 2022)
AbstractBackground: Breast tumor is a group of abnormal cells and continue growing multiply in the breast. In Indonesia, it is known that 8,1% of 38.749 women have tumor in the breast. One way to detect it early is to do the Breast Self Examination (SADARI). The purpose of the research was to know the correlation of SADARI knowledge with the size of the breast tumor at admission to surgery outpatient clinic. Methods: This type of research is observational analytic, cross sectional design. The sample were 36 tumor patients. The sampling technique was a convenient sampling. The independent variable was the knowledge SADARI and the dependent variable was the size of the breast tumor. The secondary data was taken in the form of USG and the primary data was a questionnaire. The data was tested with Spearman Rank. Results: The results of the bivariate analysis showed 0,328 (p>0,05) probability score (p value) and 0,168 R score which meant the correlation was very weak. Conclusion : there is no correlation of SADARI knowledge with the size of breast tumor at admission of surgery outpatient clinic. Keywords: Knowledge, SADARI, The size of breast tumor at admission